Subject-Spotting Experimental Method for Gen Z - Opriș, Ioana; Cenușă, Victor-Eduard (TEM Journal, 2017)
The technological changes along with the psychological and structural changes of the young generation (Gen Z) require adjustment of the educational methods. In this regard, the paper presents a way of explaining uncertainty of measurements by the use of experimental subject-spotting. The method consists in splitting – subject-spotting – a complex subject into small parts that require lower sustained attention and are easier to be understood and memorized. Each subject-spot uses the link between theory and practice, allowing multi-tasking behaviours. The focus is on obtaining quick results.The practical application of experimental subject-spotting of uncertainty is based on the measurement of the water flow through a pipe by the method of time volume collection. The flow rate measurement represents the grounding for developing several experimental subject-spots that explain the uncertainty of analogue and digital readings, of repeated measurements, the level of confidence, expanded uncertainty and the propagation of uncertainty. The mathematical model and program, some final considerations and further reading suggestions open other directions of studying uncertainty, eventually covered by other subject-spots.